Report on industrial attachment with Land Transport Authority - Cheong, Candy. (2011)
The author was involved in several projects namely the North East Line (NEL) Platform Gap Filler, Seng Kang/Punggol Light Rail Transit (SPLRT) Grab Poles, Proposed design for the C651 Trains Platform Gap Filler, Noise Study and C151 Train Temperature Measurement. Finite Element Analysis (FEA) was performed on the NEL Platform Gap Filler and SPLRT Grab Poles. Five loading cases were considered in the analysis of NEL Platform Gap Filler. The maximum stresses of the five cases are within the allowable stress of the Aluminium L-bracket of 169.57 MPa. However, further testing would be desired to achieve a more accurate result. For the FEA of the SPLRT Grab Poles, the maximum stresses on the T-shaped and L-shaped grab poles are 104.2 MPa and 85.217 MPa respectively. Given an allowable stress of 217.39 MPa, both of the grab poles are able to withstand the maximum loading. In addition, the author designed a Platform Gap Filler for the C651 trains. The noise levels of the four locations (Ang Mo Kio, Bishan, Clementi and Jurong East) were measured and further investigation of the data collected would be made. Furthermore, temperature measurements of the C151 trains were recorded and they are approximately within the desired train temperature condition except for the journey from Bishan to City Hall Stations. In conclusion, the 22 weeks of Industrial Attachment has allowed the author to better appreciate the job scope of an engineer in the Rolling Stock Division of Land Transport Authority (LTA).